Problems of Learning Arabic in Reading and Writing Skills in Nagreg Junior High School - Mochamad Nur Ichsan; Isop Syafe'i; Abdullah Husen; Muhammad Hasan; Ainun Hasyim (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
A person's language skills can be seen sequentially from four skills, namely listening, speaking, reading and writing. This skill of reading and writing Arabic is not realized to have been learned when learning to Read and Write the Qur'an. However, because it is not studied specifically in Arabic subjects, these skills are not honed properly, which is what happened at Islamic Junior High School of Matahati Nagreg. The purpose of this study is to find out the problems of Arabic learning that occur in Islamic Junior High School of Matahati Nagreg in reading and writing skills along with offering solutions that can be applied to overcome the problems that occur. The method used in this study is a descriptive method with a qualitative approach, namely by observation, interviews and documentation. The results of this study show that the problems that are being faced by Islamic Junior High School of Matahati Nagreg includes linguistic problems such as the ability to read and write Arabic letters, vocabulary, and grammatical comprehension that is still minimal. While non-linguistic problems include students, textbooks, teachers, facilities and the environment. The solution offered is to fix all these aspects so that both linguistic and non-linguistic problems can be handled efficiently and proportionally.